Positive Psychological Interventions for Patients with Type 2 Diabetes: Rationale, Theoretical Model, and Intervention Development - Jeff C. Huffman; Christina M. DuBois; Rachel A. Millstein; Christopher M. Celano; Deborah Wexler (Journal of Diabetes Research)
Most patients with type 2 diabetes (T2D) have suboptimal adherence to recommended diet, physical activity, and/or medication. Current approaches to improve health behaviors in T2D have been variably effective, and successful interventions are often complex and intensive. It is therefore vital to develop interventions that are simple, well-accepted, and applicable to a wide range of patients who suffer from T2D. One approach may be to boost positive psychological states, such as positive affect or optimism, as these constructs have been prospectively and independently linked to improvements in health behaviors. Positive psychology (PP) interventions, which utilize systematic exercises to increase optimism, well-being, and positive affect, consistently increase positive states and are easily delivered to patients with chronic illnesses. However, to our knowledge, PP interventions have not been formally tested in T2D. In this paper, we review a theoretical model for the use of PP interventions to target health behaviors in T2D, describe the structure and content of a PP intervention for T2D patients, and describe baseline data from a single-arm proof-of-concept (N=15) intervention study in T2D patients with or without depression. We also discuss how PP interventions could be combined with motivational interviewing (MI) interventions to provide a blended psychological-behavioral approach.